Une ontologie multilingue des noms propres - Denis Maurel; Mickaël Tran (Corela)
This paper describes a multilingual ontology of proper names divided into two parts, a first part shared by all the treated languages and a second part specific to each language. It includes, on the one hand, three semantic relations (Synonymy, Meronymy and Predication) and, on the other hand, some morphosyntactical information.